Utilização de firewall em aplicação de segurança e ferramentas gerenciais - Weigert, Alexsander (2017)
Information security is related to the protection of valuable data of an individual or a particular company, with the high demand in the search for information integrity and the confidentiality of systems, such as: banking transactions, scheduling a medical consultation or a Simple access to a search engine. The activities are converging to a dependence of connectivity, due to this, implementation of technologies focused on the area of security in telecommunications are in constant transformation, these evolutionary processes have relevance and importance in corporate environments. Having privacy and security in the information in a corporate environment is only possible with the right tools, coupled with a well-developed and well-publicized security policy practiced by each of the employees. With the advancement of technology, information is increasingly accessible, facilitating access to information by criminals seeking theft of confidential information, electronic diversion of resources, and congestion of services. The objective of this work is to demonstrate which tools can be used in the area of network security and the concepts of a system called firewall, for this was used an application of a unified management system called Check Point, to demonstrate how the detection and The management of these softwares, which usually operate under a unified security architecture, which allows a single agent that can be managed from a single management console.